J.M.G. Le Clézio and Jacques Derrida’s “Limitrophic,” Biocentric Deconstruction of the “Genesis Myth” - Moser, Keith (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2022)
This transdisciplinary reflection examines J.M.G. Le Clézio and Jacques Derrida’s limitrophic deconstruction of what is commonly referred to as the “genesis myth” in Judeo-Christian society. In addition to Cartesian dichotomies and debunked notions of human exceptionalism originating from Renaissance humanism, the Franco-Mauritian writer and Pied-noir philosopher take aim at the mainstream interpretation of Abrahamic cosmogonic narratives that have created a sharp ontological gap between Homo sapiens and other animals. Le Clézio and Derrida describe the genesis account of human-animal relations as an ecocidal, conflictual relationship that could be labeled a world war. They demonstrate that our dominant cognitive structures including the “genesis myth” that mostly remain uncontested, at least within the general public, have already left behind a path of irreversible destruction and other-than-human suffering. Unless we are able to curb the unending fury that the animal within us has unleashed against other sentient beings who bleed, suffer, live, and die just like us, Le Clézio and Derrida lament that our days are numbered.